Overview of Factors That Encourage Interest in Implant Contraception with the Reasoned Action Theory Approach in Non Implant Contraceptive Acceptor (In Polindes Sumekar Kapu Village, Merakurak District, Tuban Regency - erna eka wijayanti (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Today there are still many mothers who are not interested in joining Family Planning (KB). This lack of interest is due to many acceptors who are afraid of minor surgical wounds done during installation, incorrect information about implant contraceptives and lack of family support. In addition, there are other factors that cause low Mother's interest for KB Implant attitude and subjective norms. The purpose of this study is to know the description of factors that encourage interest for KB Implant With Reasoned Action Theory Approach In Non-Implant Family Planning Acceptor At Polindes Sumekar Kapu Village, Merakurak Sub-district, Tuban Regency".In this research use descriptive research design with approach of Purpose Sampling.Population that is 55 respondent KB Non Implant in August 2017. Samples are all acceptor of KB Non Implant in August which fulfill inclusive criteria in Polindes Sumekar as many as 45 respondents. The data were collected by giving questionnaires and then tabulated.Result of research from 45 respondents got all respondents have low interest (100%). Almost All KB Non Implant Acceptor has negative attitude as much as (93,3%). Almost all of the KB Non Implant Acceptors have sufficient subjective norms (77.8%). All KB Non Implant Acceptor has a negative attitude and low interest as much (100%). And all of the KB Non Implant Acceptors have sufficiently subjective and low interest (100%) norms.From the above description of the interests of mothers is very influential on the use of contraceptive devices implant. Therefore, the interests of mothers should be enhanced by communicative approach to EFA and increase the role of family, health cadres, and counseling about KB Implant.